0011 Encouraging safe physical activity: a community approach. (26th April 2015) - Wyant, Brian; Smith, Andrea
Abstract : Statement of purpose: Pennsylvania has funded five Safe and Healthy Communities whose purpose is to increase the quality, availability, and effectiveness of educational and community-based programs designed to prevent disease and improve health and quality of life. York City has utilised funding to partner with city government and planners to implement policy and environmental changes that can prevent injury and increase physical activity for city residents. Methods/Approach: Established a partnership with the Mayor's office, city planners, and other community organisations to focus on policy, environmental, and system changes that would provide safe physical activity options for all residents. Results: In August 2012, a Complete Streets policy was signed by the Mayor and a transportation taskforce was formed to identify projects that would improve city infrastructure to promote physical activity. Bike lanes and shared lane markings were installed, crosswalks have been enhanced to increase visibility, and bike racks have been installed throughout the city. A recent survey showed that 83% of residents found the environmental changes beneficial to their community. Conclusions: Through collaborative efforts and enhanced partnerships, York City has successfully increased the opportunities for safe physical activity. Utilisation of the Complete Streets policy has led to city planners looking into undeveloped sections of the city and incorporating walkable/bikeable elements into future design plans and the transportation taskforce now has 19 community organisations actively involved. Significance and contribution to the field: By incorporating physical activity into city transportation planning, residents are provided greater accessibility to safe modes of active transportation and physical activity. Increased safe physical activity will improve the overall health of a community and reduce costs to society.